STRATEGI PENINGKATAN KINERJA APARATUR SIPIL NEGARA MELALUI APLIKASI PENILAIAN KINERJA JABATAN APARATUR (SIKERJA) DI PEMERINTAH KOTA BEKASI - M. Yunus; Sayyid Umar Fiqri (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The Indonesian government to improve competence and quality of work has tried to innovate to find newconcepts or systems, in the spirit of bureaucratic reform. The Bekasi City Government has implementeda new strategy to improve the performance of ASN. The strategy is through the SIKERJA application,but their insight into performance in completing the SIKERJA application has not been optimal andASN thinks that SIKERJA is only a money-making tool. The purpose of this study was to analyze thestrategy of the Bekasi City Government regarding the Application for Apparatus Job PerformanceAssessment (SIKERJA), as well as to analyze what factors hindered the implementation of performanceimprovement in SIKERJA and to analyze the effectiveness of the SIKERJA application by the Bekasi CityGovernment ASN which was carried out at the Bekasi City Government in part of the National Unityand Political Body. This study uses qualitative methods. Data collection techniques through primarydata collection in the form of observation and interviews, and secondary data collection through librarystudies and documentation. The data analysis technique used is the Miles and Huberman model throughdata reduction, data display, and conclusion. The results of the study indicate that the strategy implemented by the Bekasi City Government regarding the SIKERJA application is going well and somechanges occur to ASN in the application of the SIKERJA application strategy such as changes in timediscipline, discipline in work, and ASN being more active in working to achieve a target. in theSIKERJA application. However, increasing human resources to be more professional and competent isstill necessary. Researchers recommend renewing the SIKERJA application as well as facilities andinfrastructure to support performing ASNs to achieve the organization's vision and mission.